Cancer-specific Mortality After Cryoablation vs Heat-based Thermal Ablation in T1a Renal Cell Carcinoma. Issue 1 (28th January 2023) - Sorce, Gabriele; Hoeh, Benedikt; Hohenhorst, Lukas; Panunzio, Andrea; Tappero, Stefano; Tian, Zhe; Kokorovic, Andrea; Larcher, Alessandro; Capitanio, Umberto; Tilki, Derya; Terrone, Carlo; Chun, Felix K. H.; et al.
Abstract : Purpose: Guidelines suggest less favorable cancer control outcomes for local tumor destruction in T1a renal cell carcinoma patients with tumor size 3.1-4 cm. We compared cancer-specific mortality between cryoablation vs heat-based thermal ablation in patients with tumor size 3.1-4 cm, as well as in patients with tumor size ≤3 cm. Materials and Methods: Within the Surveillance, Epidemiology, and End Results database (2004-2018), we identified patients with clinical T1a stage renal cell carcinoma treated with cryoablation or heat-based thermal ablation. After up to 2:1 ratio propensity score matching between patients treated with cryoablation vs heat-based thermal ablation, we addressed cancer-specific mortality relying on competing risks regression models, adjusted for other-cause mortality and other covariates (age, tumor size, tumor grade, and histological subtype). Results: Of 1, 468 assessable patients with tumor size 3.1-4 cm, 1, 080 vs 388 were treated with cryoablation vs heat-based thermal ablation, respectively. After up to 2:1 propensity score matching that resulted in 757 cryoablations vs 388 heat-based thermal ablations, in multivariable competing risks regression models, heat-based thermal ablation was associated with higher cancer-specific mortality (HR:2.02, P < . 001), relative to cryoablation. Of 4, 468 assessable patients with tumor size ≤3 cm, 3, 354 vs 1, 114 were treated with cryoablation vs heat-based thermal ablation, respectively. After up to 2:1 propensity score matching that resulted in 2, 217 cryoablations vs 1, 114 heat-based thermal ablations, in multivariable competing risks regression models, heat-based thermal ablation was not associated with higher cancer-specific mortality (HR:1.13, P = . 5) relative to cryoablation. Conclusions: Our findings corroborated that in cT1a patients with tumor size 3.1-4 cm, cancer-specific mortality is twofold higher after heat-based thermal ablation vs cryoablation. Conversely, in patients with tumor size ≤3 cm either ablation technique is equally valid. These findings should be considered at clinical decision making and informed consent.